Manual of Aquatic Sediment Sampling - Mudroch, Alena (Lewis Publishers, 1995)
This guide to aquatic sediment sampling discusses objectives, commonly used samples and techniques. Sample handling, transport, storage and costs are outlined with particular reference to the final use of the sample. The text also describes advantages and limitations of various techniques.